Given two functions f(x) and g(x)`!=0`, how can I find (f+g)(x), (f-g)(x), (f*g)(x) and (f/g)(x)

Expert Answers

An illustration of the letter 'A' in a speech bubbles

The functions we have are f(x) and g(x)`!=0` .

(f+g)(x) = f(x) + g(x)

(f-g)(x) = f(x) - g(x)

(f*g)(x) = f(x)*g(x)

(f/g)(x) = f(x)/g(x)

As g(x)`!=0`, f(x)/g(x) is always defined.

As an example take the functions f(x) = 3x + 2 and g(x) = x^2 + 1

(f+g)(x) = f(x) + g(x) = 3x + 2 + x^2 + 1 = x^2 + 3x + 3

(f-g)(x) = f(x) - g(x) = 3x + 2 - x^2 - 1 = -x^2 + 3x + 1

(f*g)(x) = f(x)*g(x) = (3x + 2)(x^2 + 1) = 3x^3 + 2x^2 + 3x + 2

(f/g)(x) = f(x)/g(x) = (3x + 2)/(x^2 + 1)

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial